2016
DOI: 10.1186/s41240-016-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of bacteriocin-producing lactic acid bacteria against histamine-forming bacteria isolated from Myeolchi-jeot

Abstract: The objectives of this study were to identify the histamine-forming bacteria and bacteriocin-producing lactic acid bacteria (LAB) isolated from Myeolchi-jeot according to sequence analysis of the 16S rRNA gene, to evaluate the inhibitory effects of the bacteriocin on the growth and histamine accumulation of histamine-forming bacteria, and to assess the physico-chemical properties of the bacteriocin. Based on 16S rRNA gene sequences, histamine-forming bacteria were identified as Bacillus licheniformis MCH01, Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The levels of other biogenic amines such as cadaverine, putrescine, tyramine, and histamine were significantly reduced by several folds in the enterocin AS-48-treated samples after storage, reviewed in (Grande Burgos et al, 2014 ). Likewise, E. faecium MCL13 was found to produce an antibacterial compound with inhibitory activity against the tested histamine-producing bacteria and exhibited histamine-degradation ability in fermented fish (Lim, 2016 ). Furthermore, the production of biogenic amines during fermentation can be controlled by the use of amine oxidizing bacteria and enzymes (Naila et al, 2010 ).…”
Section: Current Applications Of Enterococci and Their Bacteriocinsmentioning
confidence: 99%
“…The levels of other biogenic amines such as cadaverine, putrescine, tyramine, and histamine were significantly reduced by several folds in the enterocin AS-48-treated samples after storage, reviewed in (Grande Burgos et al, 2014 ). Likewise, E. faecium MCL13 was found to produce an antibacterial compound with inhibitory activity against the tested histamine-producing bacteria and exhibited histamine-degradation ability in fermented fish (Lim, 2016 ). Furthermore, the production of biogenic amines during fermentation can be controlled by the use of amine oxidizing bacteria and enzymes (Naila et al, 2010 ).…”
Section: Current Applications Of Enterococci and Their Bacteriocinsmentioning
confidence: 99%
“…Histamine is more likely to be produced where storage temperatures are above 15°C, as histamine formation is mostly determined by mesophilic bacteria (Torido et al., 2014). A study identifying histamine‐forming bacteria and bacteriocin‐producing LAB in myeolchi ‐ jeot , a fermented Korean seafood, discovered that the bacteriocins produced inhibited the growth of the histamine‐producing bacteria (Lim, 2016). This may indicate that safe fermentation, which encourages histamine degrading LAB, along with appropriate storage after fermentation will reduce contamination by biogenic amines, such as histamine.…”
Section: Potential Food Safety Hazards In Japanese Koji and Misomentioning
confidence: 99%
“…FTIR analysis of the purified products of H4 bacteriocins showed an amide bond at a wavelength of 1652 cm-1 which indicated that the compound was a protein. Bacteriocins produced from the laboratory isolates may be useful as a food preservative for controlling microbial deterioration, enhancing the hygienic quality, and extending the self-life of fish and seafood products 27 .…”
Section: Discussionmentioning
confidence: 99%